La politique sanitaire des autorités héraultaises à l’égard des réfugiés espagnols de la guerre civile - Vincent Parello (Les Cahiers de Framespa)
The city of Montpellier and its region acted like a real «hospital departement» towards the Spanish refugees who came from Perpignan and Marseille.In collaboration with the health and hygiene authorities, the Prefect of Hérault set up three centers in his department: the sanitary center A for the region of Montpellier, the sanitary center B for the region of Sète and the sanitary center C for the region of Béziers. It was necessary to protect the refugees and the local populations against tuberculosis, infectious and venerian diseases.